독일에서의 침술 건강보험 급여화 사례 연구 - 김동수; 박인효; 임병묵; Kim, Dongsu; Park, Inhyo; Lim, Byungmook (대한예방한의학회지, 2019)
Background : Germany is the first country in the world to introduce modern systems of public health insurance, and the country which most widely uses complementary alternative medicine(CAM) in Europe. In early 21st century, a large evaluation studies were conducted to include acupuncture in health insurance payments, which were eventually decided. Objectives : This study is to investigate and analyze the process of public policy determination on insurance coverage for acupuncture in German health insurance system. Methods : We collected the data and information through the literature search and from the websites of German government departments and health insurance organizations. To obtain contextual information, German experts of health insurance and acupuncture clinical study were interviewed. Results : As use of acupuncture had been growing, German public health insurers wanted to evaluate the validity of acupuncture coverage and sponsored three evaluation projects for clinical effectiveness of acupuncture using randomized clinical trials, systematic reviews, and pragmatic trials from 2001 to 2005. For some pain condition, acupuncture was founded not to be effective than sham acupuncture, but more effective than standard care. The federal joint committee of health insurance decided to cover acupuncture for chronic pain of lumbar spine and chronic pain in at least one knee joint due to gonarthrosis. Conclusions : Considering the controversial subject matter in the process of acupuncture's health insurance coverage in Germany, expanding the benefits of Korean medicine in Korea needs to come up with ways to overcome the difficulties of placebo effect, standardization and lack of literature evidence.